If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7 + 10y = -14 Solving -7 + 10y = -14 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 10y = -14 + 7 Combine like terms: -7 + 7 = 0 0 + 10y = -14 + 7 10y = -14 + 7 Combine like terms: -14 + 7 = -7 10y = -7 Divide each side by '10'. y = -0.7 Simplifying y = -0.7
| (((x^1/2)*(y^-2))/((y)*(x^-7/4)))^4 | | 3x-3(4x+5x)=0 | | 2y/7-7/8=13/56 | | 3/4x1/2=-1/4x-1/4 | | 17=4-2n+5 | | -7v+5(1-6v)=301 | | X/4=-1.25 | | a=0.008(150) | | 1/3x-4=9/7-5/6x | | 3x-8x+66=2x+31 | | 6t^2+4=2t^2 | | ln(x)=3.29 | | 20x^2-82x+42=0 | | 2=y/2-3 | | (2x^6y^-5/5x^-4y^3)^-2 | | 45=60p | | 9m=-81 | | x-39/4=3/2 | | 4+1(1+3x)5= | | 4j-13j+10j=-17 | | -6m+2=3y-5 | | 5k-6+6k-22=3 | | 20x+4=8x+52 | | 1r+1r+1r+1r=1r | | 6m-11-am=1 | | (2x+1)+(x-13)=180 | | 9e^9x=2 | | 0=2x^3-4x^2-150 | | 102=1.2w | | 3d+3d+3d-9d=12 | | 12=0.005w | | 9/6=15/2 |